The impact of technological development on the conclusion of a marriage contract - Yebdri, Rabia (The International tax journal, 2026)
The family is the foundation of building societies in all nations, and the marriage contract is regarded as the covenant upon which the family is established. This contract serves as the essential bond between a man and a woman, and, therefore, the Algerian legislator, like other legislators, has provided it with a special legal framework within the provisions of Algerian Family Law. Given that the marriage contract is a type of contract entered into through a specific legal procedure, it is also subject to scientific advancements in technology, which have led to the emergence of what is known as "electronic marriage." This development has prompted Islamic jurisprudence and legal experts to examine the validity of this contract, considering the lack of a clear legal basis in this regard, which is the focus of this study.